Diversities, affinities and diasporas: a southern lens and methodology for understanding multilingualisms. Issue 1 (1st January 2019) - Heugh, Kathleen; Stroud, Christopher
ABSTRACT: We frame multilingualisms through a growing interest in a linguistics and sociology of the 'south' and acknowledge earlier contributions of linguists in Africa, the Américas and Asia who have engaged with human mobility, linguistic contact and consequential ecologies that alter over time and space. Recently, conversations of multilingualism have drifted in two directions. Southern conversations have become intertwined with 'de-colonial theory', and with 'southern' theory, thinking and epistemologies. In these, 'southern' is regarded as a metaphor for marginality, coloniality and entanglements of the geopolitical north and south. Northern debates that receive traction appear to focus on recent 're-awakenings' in Europe and North America that mis-remember southern experiences of linguistic diversity. We provide a contextual backdrop for articles in this issue that illustrate intelligences of multilingualisms and the linguistic citizenship of southern people. In these, southern multilingualisms are revealed as phenomena, rather than as a phenomenon defined usually in English. The intention is to suggest a third direction of mutual advantage in rethinking the social imaginary in relation to communality, entanglements and interconnectivities of both South and North.